2012
DOI: 10.1177/0148607112458798
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Oral Administration of Cystine and Theanine Enhances Recovery After Distal Gastrectomy

Abstract: Appropriate regulation of inflammation during the perioperative period is important for achieving a stable postoperative course and early recovery and for reducing the malignancy relapse rate. For these reasons, an immune-modulating diet that includes anti-inflammatory substances such as ω-3 fatty acids has been used widely in clinical settings. The amino acids cystine and theanine are both involved in the synthesis of glutathione (GSH), a strong antioxidant, and there have been several reports that oral cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…The need for GSH is thought to increase under these conditions. We previously described that the intake of cystine and theanine for 10 days during the perioperative period led to the early resolution of high postoperative levels of interleukin (IL)-6 and C-reactive protein (CRP) and early recovery from changes in neutrophil and lymphocyte counts [8]. Cystine and theanine has also been shown to produce similar effects in mouse digestive tract surgery models and to prevent decreases in intestinal GSH; these effects were considered to be partly explained by the supply of GSH [9].…”
Section: Introductionmentioning
confidence: 99%
“…The need for GSH is thought to increase under these conditions. We previously described that the intake of cystine and theanine for 10 days during the perioperative period led to the early resolution of high postoperative levels of interleukin (IL)-6 and C-reactive protein (CRP) and early recovery from changes in neutrophil and lymphocyte counts [8]. Cystine and theanine has also been shown to produce similar effects in mouse digestive tract surgery models and to prevent decreases in intestinal GSH; these effects were considered to be partly explained by the supply of GSH [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found a link between the synergistic effect of L-THE and cysteine in ameliorating inflammatory responses in the intestinal tract [76]. Miyachi et al [76] demonstrated that the co-treatment of L-THE (280 mg) and cysteine (700 mg) post-surgery alleviated post-gastrectomy inflammation.…”
Section: Immune Systemmentioning
confidence: 99%
“…In addition, oral administration with L-theanine and L-cystine before vaccination can enhance the immune response to influenza vaccine in elderly persons with low haemoglobin [53]. Oral administration of L-cystine and L-theanine during the perioperative period alleviates post-gastrectomy inflammation and promotes recovery after surgery [54]. Supplementation of L-cystine and L-theanine significantly suppresses the exercise-induced fluctuation of blood immunocompetent cells, and helps to reduce alterations of the immune response by both attenuating the rise of neutrophil count and reducing the lymphocyte count caused by extreme endurance exercise [55][56][57].…”
Section: Improving Immunitymentioning
confidence: 99%